THE COMPOSITION OF THE LINGUISTIC COMPONENT OF THE CONTENT OF TEACHING THE GRAMMATICAL SIDE OF SPEECH IN A FOREIGN LANGUAGE - Almatova Umida Islamovna; Kamolova Saida Zufar qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotatsion: This article considers the composition of the linguistic component of the content of teaching the grammatical side of speech in a foreign languages at the university. The goals of teaching a foreign language are an important methodological category. The starting point in determining the strategic goal of education is the social order of society in relation to the younger generation.